The role of literature in intercultural language education - Melina Porto; Michalinos Zembylas (Intercultural Communication Education)
In this article we discuss how the design of a higher education language course can challenge the power of sentimentality in the classroom. In particular, the paper analyses the role of literature in intercultural language education through the lens of affect theory, while focusing on minimizing sentimentality in the classroom, especially when the literary texts used confront students with trauma-related content involving human rights abuse, death and suffering, and trigger discomforting emotions in students such as sadness, anguish, fear and more. We suggest that it is important for educators and students in higher education to recognize the affective and biopolitical dimensions of literature teaching in intercultural language education. This is illustrated through the design of an English language course syllabus in an Argentinian higher education setting. The paper concludes with a discussion of the curricular and pedagogical implications for intercultural language education.